Entrepreneurship in the Philippines: 2014 report - Velasco, Aida L. (Animo Repository, 2016)
The Philippine sample from 2014 Global Entrepreneurship Monitor comprised of 2,000 individuals, aged 18-64, representing 17 regions in the country, and 36 national experts. Respondents were interviewed according to a framework that considered both the individual and institutional conditions of entrepreneurship. For this year's Report, we consider more closely the prospects of micro- and youth entrepreneurship in alleviating poverty and unemployment within the country. In the last few years, research particularly by Banerjee and Duflo at MIT's Poverty Action Lab has suggested that some of the optimism about entrepreneurship as a bridge out of poverty in developing countries has been misplaced, and that entrepreneurial success is harder to come by than frequently believed. We find broad support for these ideas Philippine survey, and use this as an opportunity to rethink entrepreneurship strategy and policies in the country. SELECTED KEY FINDINGS 1. Within ASEAN, Philippine respondents registered the strongest entrepreneurial intentions, perceptions of personal capabilities and market opportunities, as well as the lowest fear of failure. This matches the high social regard for entrepreneurs within the Philippines; 2. These motivations have translated into the highest of new business formation or "nascent entrepreneurship" the region, and the second-highest rate of early-stage entrepreneurship; 3. These encouraging statistics are tempered by the highest rate of business discontinuance in the region. The leading reasons for this are low profitability, depletion of capital, and personal emergencies;4.Furthermore, there is reason to be concerned over the basis for long-term entrepreneurial success. Many respondents admit turning to entrepreneurship because of a lack of options in the formal labor market. Many also admit to selling products for which many competitors already exist, and data show very low levels of international market penetration. Entrepreneurial success, in the sense of crossing the threshold from micro-to small, and from small to medium enterprise, is still held back by these deficiencies. RECOMMENDATIONS 1.Continued expansion of social insurance and anti-poverty programs such as 4Ps, especially those with a gender component. Apart from their impact on education and health, these programs directly improve entrepreneurial conditions by reducing the hidden costs of running a business and the risks of business failure. As in many developing countries, progress can be made by solving "last mile" problems of poor coordination and lack of awareness, by better-designed interventions that make it easier for individuals lo help themselves; 2.More emphasis on "second-generation" problems of entrepreneurial survival and growth, rather than "first-generation" across-the-board encouragement for potential entrepreneurs. Public agencies may wish to focus more resources on selecting "winners" with the greatest potential for innovating, scaling up, and penetrating international markets, rather than funding as many start-ups as possible, or providing basic training. Along with this should come more interventions lo encourage pooling resources and risk, rather than relying on the limited network of one's family and friends, as most micro-entrepreneurs still do; 3.Finally, with educational reforms creating an entrepreneurship track for the youth, the message must be balanced: success is possible, but innovation and internationalization are key; remaining a micro-enterprise means that a business is perpetually at risk.